A soft X-ray unipolar charger for ultrafine particles. (July 2019) - Chen, Xiaotong; Jiang, Jingkun; Chen, Da-Ren
Abstract: The performance of a unipolar particle charger using soft X-ray as the ion production source was optimized and characterized in this study. The charger design was based on the high efficiency particle charger reported by Chen and Pui (1999), in which the radioactive material ( 210 Po) as the ion source and sheath flow for minimizing the particle loss were used. The use of 210 Po source makes it challenging for field investigation due to the regulation of controlled substances. The inclusion of sheath flow in the high efficiency charger inevitably dilutes the output particle concentration, which is an undesired effect for the measurement of atmospheric ultrafine particles. The current soft X-ray charger was designed to ease the above concerns. The penetration efficiency, intrinsic and extrinsic charging efficiency, and extrinsic charge distributions of particles passing through the charger were measured under the optimal voltage operation. It was found that the loss of ultrafine particles in the charger was higher than that in the high efficiency charger (due to the lack of applying sheath flow). At the flow rate of 5.0 lpm, the measured extrinsic charging efficiency was comparable to that of the charger applied in the thermal desorption chemical ionization mass spectrometer (Smith et al., 2004). The measured extrinsic charge distribution of particles further showed that more than 50% of particles in the size range of 20–40 nm and 20–50 nm were singly charged at the flow rate of 1.5 lpm and 5.0 lpm, respectively.